Water Conservation Benefits of Long‐Term Residential Irrigation Restrictions in Southwest Florida. Issue 2 (12th February 2018) - Boyer, Mackenzie J.; Dukes, Michael D.; Duerr, Isaac; Bliznyuk, Nikolay
Abstract : Long‐term watering restrictions for single‐family residential customers in southwest Florida coincided with lower irrigation. Irrigation demand (landscape water applied) was estimated from monthly water billing records of approximately 127, 250 customers from 1998 to 2010. Mean monthly irrigation demands under restrictions that limited irrigation to two days/week and one day/week were calculated for each customer and summed to yield annual irrigation demands. Annual irrigation demand was 13% lower (9.8 versus 11.3 in./year), while the irrigation required by the landscape as a result of weather conditions was 3% higher (25.7 versus 25.0 in./year) under the more stringent restrictions. The majority of customers irrigated less than their landscape required. High irrigators (those irrigating above what their landscape required) irrigated 20% less (10.2 in./year) under the more stringent conditions, indicating that those who irrigated most had the highest conservation potential. Additional conservation potential existed for high irrigators, whose irrigation demand exceeded landscape requirements by 56% under one day/week restrictions.